Hajj health examination for pilgrims with asthma in Malaysia: an ethnographic study - Ramli, Rizawati; Hanafi, Nik Sherina; Hussein, Norita; Lee, Ping Yein; Shariff Ghazali, Sazlina; Cheong, Ai Theng; Abu Bakar, Ahmad Ihsan; Abdul Samad, Azah; Abdullah, Suhazeli; Pinnock, Hilary; Sheikh, Aziz; Khoo, Ee Ming (University of Edinburgh, 2022)
Background Asthma was one of the top causes of hospitalization and unscheduled medical attendances due to acute exacerbations and its complications. In Malaysia, all pilgrims must undergo a mandatory health examination and certified fit to perform pilgrimage. We studied the current organisational and clinical routines of Hajj health examination in Malaysia with a focus on the delivery of care for pilgrims with asthma. Methods We conducted non-participant observation to obtain ethnographic understanding of Hajj health examination activities for 2019. Observations were guided by a checklist and recorded as notes that were analysed thematically. The study was conducted at 11 public (from each region in Malaysia, namely, North, South, East, West of Peninsular Malaysia, and Sabah and Sarawak of East Malaysia) and two private primary care clinics. Results We observed considerable variation in the implementation and practice of Hajj health examinations among the 11 public clinics but no marked variation among the private clinics. The short time span of between three to four months was inadequate for disease control measures and had put pressure on health care providers. They mostly viewed the Hajj health examination as merely a certification of fitness to perform the pilgrimage, though respiratory health assessment was often inadequate. The opportunity to optimise the health of pilgrims with asthma by providing the appropriate medications, asthma action plan and asthma education including the preventive measures was disregarded. The preliminary health screening, which aimed to optimise pilgrims’ health before the actual Hajj health examination was not appreciated by either pilgrims or health care providers. Conclusions There is great potential to reform the current system of Hajj health certification in order to optimise its potential benefits for pilgrims with asthma. A systematic approach to restructuring the delivery of Hajj health examination could address the time constraints, clinical competency of primary health care providers and resources limitations.